Korelasi Prestasi Belajar Pendidikan Agama Islam Dengan Akhlak Siswa Terhadap Guru Di SMP Muhammadiyah 01 Medan - Dessy Ariani Hasibuan (-, 2023)
This study aims to determine whether there is a correlation between learning achievement in Islamic Religious Education and students' morals towards teachers at SMP Muhammadiyah 01 Medan. The method used in this study is a quantitative research method, with a type of correlational research, and a deductive research approach. The results of his research found that there was no correlation between learning achievement in Islamic Religious Education and student morals towards teachers at SMP Muhammadiyah 01 Medan, although between Islamic Religious Education learning achievement was positively related to student morals towards teachers with a strong correlation category.